IMPACT OF FREE TRADE AGREEMENTS ON INDONESIA ECONOMIC PERFORMANCES - Muchtar Muchtar (Universitas Trisakti, 2015)
Indonesia participates in various free trade agreements with its main trading partners and it raises a research problem namely whether the participation would create benefits for Indonesia economic performances. Then, the research problem generates research questions that are what are the impacts of free trade agreements several aspects particularly for economic, social, and environment.Main objectives of this research will focus to assess the impacts of free trade agreements on: (i) economic aspects such as economic growth, export and import performances, balance of trade, terms of trade, investment, inflation, government expenditure and consumption, and sector output; (ii) social aspect such as labor market, wages, income gap between skilled and unskilled labor, social welfare; and (iii) environment aspect.Method of the research employs an economic model of computable general equilibrium on international trade, namely Global Trade Analysis Project (GTAP Model 8 version). There are two policy simulations of tariff reduction namely; (i) Simulation I, tariff of agriculture products reduced by 65% and tariff of non-agriculture products reduced by 85%; (ii) Simulation II, tariff of agriculture products reduced by 80% and tariff of non-agriculture products reduced by 100% The research found that in general, impact of free trade agreement benefit for Indonesia economic performances, it indicated by economic variables that contribute positively to the economic performances are greater than economic variables that contribute negatively to the economic performances. The positive economic variables are economic growth, export performance, terms of trade, balance of trade, investment, government expenditure and consumption, wages, social welfare. While the negative economic variables are import performance, inflation, sector output, labor market, income gap of skilled and unskilled labors, emission proliferation.Research limitations related to the secondary data sources that depend on data published by international and national institutions as well as the data that already embodied in the GTAP Model. Policy implication to the government policy namely: (i) to undertake economic and trade reform to improve competitiveness; (ii) to undertake deeply comprehensive study before participation in the FTA; (iii) to give assistances for loser business particularly for small and medium enterprises; (iv) to socialize actively about the FTA to related business community.